Lost Saints: Desacralization, Spiritual Abuse and Magic Mushrooms - Lutkajtis, Anna (Fieldwork in religion, 2019)
Mushrooms containing psilocybin have been used in Indigenous healing ceremonies in Mesoamerica since at least the sixteenth century. However, the sacramental use of mushrooms was only discovered by Westerners in the early to mid-twentieth century. Most notably, the meeting between amateur mycologist Robert Gordon Wasson and Mazatec curandera María Sabina in 1955 resulted in the widespread popularization of ingesting "magic mushrooms" in the West. To Sabina and the Mazatec people, psilocybin mushrooms were sacred and only to be used for healing. However, Western "hippies" viewed mushrooms as psychedelic drugs which they consumed with little regard for cultural sensitivities, rendering the mushrooms desacralized. This article argues that the desacralization of psilocybin mushrooms constitutes a form of spiritual abuse that has had far-reaching and long-lasting consequences at individual, local and global levels. Further, acknowledging and understanding the desacralization of psilocybin mushrooms as spiritual abuse has important implications for restorative justice and the understanding of psilocybin as a sacred medicine.